A Comparison of Poverty Rate Estimates Using Expenditure and Income Data - Panos Tsakloglou (Luxembourg Income Study (LIS), 1991)
This is a comparative study of poverty rate estimates in five EEC countries. The study compares the poverty estimates from that carried out for Eurostat by the Institute of Social Studies Advisory Service (ISSAS (1990)) with those derived using the income data of the Luxembourg Income Study database.
Keywords: 330